2019
DOI: 10.1016/j.firesaf.2019.102827
|View full text |Cite
|
Sign up to set email alerts
|

The Malveira fire test: Full-scale demonstration of fire modes in open-plan compartments

Abstract: This paper aims to characterize dynamics of a fire in the Large-Scale Demonstrator Malveira Fire Test, a full-scale fire experiment carried out in a disused industrial building in Portugal. The Malveira Fire Test is the second stage in the series of full-scale experimental programmes developed for the Real Fires for the Safe Design of Tall Buildings project at the University of Edinburgh. This experiment is intended to act as a real-building demonstration of fire dynamics in large open-floor plan compartments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 21 publications
5
46
0
Order By: Relevance
“…Experiments in large enclosures showed that the fire dynamics are defined by the velocity of a propagating flame front (𝑉 " ), and the velocity of a propagating burnout front (𝑉 $% ) [5]. Based on the relationship between the flame front and burnout front (𝑉 " /𝑉 $% ), three fire spread modes were identified [6]:…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in large enclosures showed that the fire dynamics are defined by the velocity of a propagating flame front (𝑉 " ), and the velocity of a propagating burnout front (𝑉 $% ) [5]. Based on the relationship between the flame front and burnout front (𝑉 " /𝑉 $% ), three fire spread modes were identified [6]:…”
Section: Introductionmentioning
confidence: 99%
“…These modes are differentiated by their characteristic relationship between the spread velocity of the fire front and the spread velocity of the burnout front. These fire spread modes were experimentally demonstrated in the Malveira Fire Test [8], producing different levels of characteristic thermal behaviour for each mode. It was postulated that each fire spread mode and the transitions between the modes are determined by the spatial distribution of energy in the compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Travelling fires have been observed in several structural failures especially from 2000: the World Trade Center Towers [3] in New York City in 2001, the Windsor Tower [4] in Madrid in 2005, and the Faculty of TU Delft Architecture building [5] in Netherlands in 2008. The recent years have seen growing interest in investigating travelling fires which underlined the inadequacy of uniform heating in large compartments [6][7][8][9][10][11]. Further research effort is still…”
Section: Introductionmentioning
confidence: 99%